Hubungan Lingkungan Dan Sosial Budaya Dengan Stress Kerja Perawat - Alivia Intan Fahrully; Solehudin Solehudin; Lannasari Lannasari (Lembaga Pengembangan Kinerja Dosen, 2024)
Indonesian nurses in Japan have pressures such as language barriers, culture, halal food for Muslims and long working hours which will make it difficult to find prayer time, these things which make it difficult for Indonesian workers will certainly have an impact on mental health, while the region, style life. and jobs that can cause stress and anxiety. The aim of the research is to determine the relationship between environment and socio-culture with the work stress of Indonesian nurses in Japan. This research method is correlation analysis with a cross sectional study design. Respondents totaled 40 people using the total sampling method. Using 3 questionnaires, namely Depression Anxiety Stress Scale 21 (DASS 21), Multidimensional Scale of Perceived Social Support (MSPSS), and Revised Sociocultural Adaptation Scale (SCAS-R) questionnaire. Statistical analysis uses the Chi-Square test. The research results showed that the relationship between the environment and the work stress level of Indonesian nurses in Tokyo, Japan obtained a p-value of 0.002. The socio-cultural relationship with nurses' work stress levels obtained a p-value of 0.001. The conclusion is that there is an environmental and socio-cultural relationship with the work stress level of Indonesian nurses in Tokyo, Japan.